Analisis Nilai Moral dalam Naskah Drama Becik Nitik Ala Pilara Karya M. Ahmad Jalidu - Nazhiifah, Rifda Ummu; Saddhono, Kundharu; Said, Dewi Pangestu (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2023)
The spread of moral issues in the community such as the use of narcotics and illegal drugs, pornography, brawls, rape, and so on are social issues of concern and have not been resolved. Drama script is one of the literary works that can be used as a tool to instill morals in the community in an effort to solve the problems that occur. This study aims to describe the representation of moral values in the drama script "Becik Nitik Ala Pilara" by M. Ahmad Jalidu. This study uses a descriptive qualitative method with document analysis techniques. The data source of this research is the Becik Nitik Ala Pilara drama script by M. Ahmad Jalidu, the data is in the form of quotes contained in the script itself. The data analysis technique used is the flow analysis technique consisting of (1) data collection, (2) data purification or reduction, (3) data presentation, and (4) drawing conclusions. The results of this study indicate that there are five types of moral values contained in the Becik Nitik Ala Pilara manuscript by M. Ahmad Jalidu, including: (1) tolerance, (2) respect, (3) kindness, (4) self-control, ( 5) justice.